Development of Islamic Religious Education Learning Model based on Multicultural Values - Amiruddin Amiruddin; Askar Askar; Yusra Yusra (Department of Islamic Education, Postgraduate Program State Institute for Islamic Studies Palu, 2019)
The focus of this study is to examine the design development of multicultural value-based Islamic education learning models at the high school level. This research is qualitative research. Data collection is done by observation, interview, and documentation. While the data analysis technique used is data reduction, data presentation, data verification, and drawing conclusions. The results of the study showed that, the design of the development of the learning model that determined multicultural values, which were integrated in the Islamic Religious Education subject, b) syllabus, c) lesson plan, d) used the Islamic education learning model based on multicultural values, and c) conducted an assessment towards the process of learning activities, which is a follow-up to learning, the approach to developing learning models, namely the approach to justice and equality without discrimination, called cultural pluralism, which provides opportunities and freedom for all elements to show and develop their respective identities, both from language, ethnicity, religion and so on. While developing models of Islamic education learning based on multicultural values ​​because; a) multicultural education is not a special subject, b) promotes equality between students of different backgrounds, c) the diversity of students that causes misunderstandings that can lead to disputes between fellow students.